Old Colony Mennonites in Argentina and Bolivia. Nation Making, Religious Conﬂict and Imagination of the Future - Aimar Ventsel (Journal of Ethnology and Folkloristics)
Review for the book by Lorenzo Canás  Bottos, Old Colony Mennonites in Argentina and Bolivia. Nation Making, Religious Conﬂict and Imagination of the Future. Leiden, Boston: Brill 2008, 216 pages.